90.1k views
1 vote
Solve S= lw + wh+ lh for h. Hint: Use the distributive property to factor out h.

the
vcloc

User Bbedward
by
6.2k points

1 Answer

0 votes

Answer:


{ \rm{S = lw + wh + lh}}

• Group the h terms by organised term arrangement :


{ \rm{S = (wh + lh) + lw}}

• Then using distributive property, factorise out the value h so that the reverse is true.


{ \rm{S = h(w + l) + lw}}

• for the variable "lw", divide it by h in order to add it to the bracket of (w + l). Make sure the reverse is true:


{ \rm{S = h(w + l) + h( (lw)/(h) )}} \\

• finally, completely factorise out the value h


\hookrightarrow \: \: { \boxed{ \boxed { \rm{ \: \: S = h(w + l + (lw)/(h) ) \: \: }}}}

User Jeppe
by
6.0k points